Enhancement of IUdR Radiosensitization by Low-Energy Photons Results from Increased and Persistent DNA Damage - Bayart, Emilie (PLoS One, 2017)
Low-energy X-rays induce Auger cascades by photoelectric absorption in iodine present in the DNA of cells labeled with 5-iodo-2’-deoxyuridine (IUdR). This photoactivation therapy results in enhanced cellular sensitivity to radiation which reaches its maximum with 50 keV photons. Synchrotron core facilities are the only way to generate such monochromatic beams. However, these structures are not adapted for the routine treatment of patients. In this study, we generated two beams emitting photon energy means of 42 and 50 keV respectively, from a conventional 225 kV X-ray source. Viability assays performed after pre-exposure to 10 μM of IUdR for 48h suggest that complex lethal damage is generated after low energy photons irradiation compared to (137)Cs irradiation (662KeV). To further decipher the molecular mechanisms leading to IUdR-mediated radiosensitization, we analyzed the content of DNA damage-induced foci in two glioblastoma cell lines and showed that the decrease in survival under these conditions was correlated with an increase in the content of DNA damage-induced foci in cell lines. Moreover, the follow-up of repair kinetics of the induced double-strand breaks showed the maximum delay in cells labeled with IUdR and exposed to X-ray irradiation. Thus, there appears to be a direct relationship between the reduction of radiation survival parameters and the production of DNA damage with impaired repair of these breaks. These results further support the clinical potential use of a halogenated pyrimidine analog combined with low-energy X-ray therapy.